Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1016/j.drugalcdep.2013.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Drug-related stimuli impair inhibitory control in cocaine abusers

Abstract: Background Cocaine users show impaired inhibitory control on cued go/no-go tasks and attention bias to drug-related images in eye-tracking tasks. The results of a previous study suggested that there is a relationship between inhibitory control and attention bias in alcohol drinkers such that the presentation of alcohol-related images as a go cue in a cued go/no-go task significantly impaired inhibitory control compared to neutral images as a go cue. The present study determined the generality of these previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 9 publications
(23 reference statements)
3
39
0
1
Order By: Relevance
“…Once participants made a response within 2000 ms (or did not make any response after 2000 ms), feedback was presented for 1000 ms. A 500 ms black screen was presented between trials (inter-trial-interval). We selected gaming-related pictures as Go stimuli and neutral pictures as No-Go stimuli based on data suggesting that individuals with addictions may have particular difficulty in inhibiting prepotent responses within the context of addiction-specific stimuli (Pike et al, 2013). Participants performed 10 practice trials before 100 formal trials, in which each picture was presented 5 times randomly and the ratio of the Go trials to No-Go trials was 3:1.…”
Section: Participantsmentioning
confidence: 99%
“…Once participants made a response within 2000 ms (or did not make any response after 2000 ms), feedback was presented for 1000 ms. A 500 ms black screen was presented between trials (inter-trial-interval). We selected gaming-related pictures as Go stimuli and neutral pictures as No-Go stimuli based on data suggesting that individuals with addictions may have particular difficulty in inhibiting prepotent responses within the context of addiction-specific stimuli (Pike et al, 2013). Participants performed 10 practice trials before 100 formal trials, in which each picture was presented 5 times randomly and the ratio of the Go trials to No-Go trials was 3:1.…”
Section: Participantsmentioning
confidence: 99%
“…However, it must be noted that all the studies on inhibitory control utilize neutral versions of the Go/No-Go task or the Stroop paradigm. Results may be clearer if stimuli explicitly depicting Internet-related content were used, since it may be assumed that subjects with a specific Internet addiction have difficulty in inhibiting responses to stimuli representing their first-choice-use, as has been shown in binge drinkers (Czapla et al 2015) and substance-dependent individuals (e.g., Pike et al 2013). Zhou et al (2012) used a shifting task with Internet gaming-related cues and reported that reductions in response inhibition and mental flexibility can occur when addicted individuals are confronted with such addiction-specific cues.…”
Section: Neurocognitive Mechanisms Potentially Underlying Internet Admentioning
confidence: 97%
“…This suggests that anti-saccade trials require an initial inhibition of reflexive orienting, which is then followed by a generation of a voluntary saccade to the opposite hemifield (Unsworth et al, 2011). Many studies have shown that individuals who engage in longstanding abuse of cocaine develop deficits in inhibitory control (Lane et al, 2007;Fillmore et al, 2013), therefore anti-saccade errors would be expected in this population. In following with the main hypotheses of the study, cocaine-dependent subjects made more overall anti-saccade errors indicating a deficit in inhibitory control, as well as more errors, specifically on trials with cocaine stimuli compared to neutral stimuli, indicating a strong attentional bias toward drug cues.…”
Section: Discussionmentioning
confidence: 99%
“…Cocaine related stimuli have been shown to impair inhibitory control, a frontally controlled action, in cocaine dependent individuals (Pike et al, 2013). Therefore impairments to these frontal areas cause difficulty in proper execution of this task resulting in loss of attentional control and latencies in anti-saccade reaction times.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation